Levetiracetam, Attention Deficits and Subclinical EEG Spikes - J Gordon Millichap (Pediatric Neurology Briefs)
The effects of levetiracetam on neuropsychological functioning in six children (mean age 9.8 years) with attention and learning difficulties and subclinical EEG spikes without clinical seizures were determined in a prospective, open-label pilot study at the Clinical Research Center of New Jersey and Drexel University, Philadelphia, PA.